2004
DOI: 10.1016/s1090-3801(03)00064-8
|View full text |Cite
|
Sign up to set email alerts
|

The course of non‐malignant chronic pain: a 12‐year follow‐up of a cohort from the general population

Abstract: The high prevalence of chronic pain (duration >3 months) reported from different populations indicates a public health problem. Knowledge of the long-term course of chronic non-malignant pain is incomplete and scarce. This paper describes a follow-up of a cohort recruited from a survey in the general population. The cohort (n=214) consisted initially of individuals with widespread or located (neck-shoulder) pain or without chronic pain. The individuals were initially examined and replied to questionnaires on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
106
2
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 19 publications
18
106
2
6
Order By: Relevance
“…Reporting >90 days with NSP the past three months was of particular prognostic value for severe persistent NSP, which is consistent with previous reports (7). People with NSP often report comorbidity of pain in other body sites, which has been associated with a poor prognosis (36,37). However, we found that comorbidity of pain at baseline was not a significant predictor for any trajectory class in the multivariate model.…”
Section: Symptom Characteristics and Individual Predictors Of Pain Trcontrasting
confidence: 76%
See 1 more Smart Citation
“…Reporting >90 days with NSP the past three months was of particular prognostic value for severe persistent NSP, which is consistent with previous reports (7). People with NSP often report comorbidity of pain in other body sites, which has been associated with a poor prognosis (36,37). However, we found that comorbidity of pain at baseline was not a significant predictor for any trajectory class in the multivariate model.…”
Section: Symptom Characteristics and Individual Predictors Of Pain Trcontrasting
confidence: 76%
“…Prognostic studies indicate that current or past symptoms, eg, the occurrence, intensity and duration of NSP and comorbidity of pain in other body sites, predict future NSP (6)(7)(8)36). This was corroborated by the present study showing that the NSP characteristics at baseline accounted for 54% of the variance in explaining NSP trajectories.…”
Section: Symptom Characteristics and Individual Predictors Of Pain Trmentioning
confidence: 99%
“…8,24 Indeed, chronic pain can be classified as regional or widespread, depending on the number of pain sites affected. 2,7,23 Regional pain appears as single pain sites in, e.g., lower back, shoulder, or neck, with lower back and neck pain as the most frequently reported sites, 11,24 whereas widespread pain has commonly been categorized as pain in the trunk, in upper and lower limbs, and on both sides of the body.…”
Section: Introductionmentioning
confidence: 99%
“…Många med långvarig smärta söker vård, beräkningar som gjorts visar att 20-40 % av besöken i primärvården har varit föranledda av smärta, av dessa är ca hälften långvarig smärta (8). När smärtan väl är etablerad är möjligheterna till smärtfrihet relativt små (9). Mycket tyder på att tidig rehabilitering är av största vikt (5).…”
Section: Förekomstunclassified
“…Det fysiska obehaget leder till att individen inte längre känner igen sin kropp. Frågor väcks hur hon eller han ska kunna agera i och handskas med sin sociala och fysiska omgivning (9)(10)(11)(12)(13)(14). Värken kommer att styra uppmärksamheten och därmed också existensen (50).…”
Section: Det Biografiska Perspektivetunclassified